Increased MSX level improves biological productivity and production stability in multiple recombinant GS CHO cell lines - Tian, Jun; He, Qin; Oliveira, Christopher; Qian, Yueming; Egan, Susan; Xu, Jianlin; Qian, Nan‐Xin; Langsdorf, Erik; Warrack, Bethanne; Aranibar, Nelly; Reily, Michael; Borys, Michael; et al. (Engineering in life sciences, 2020)
Increasing cell culture productivity of recombinant proteins via process improvements is the primary focus for research groups within biologics manufacturing. Any recommendations to improve a manufacturing process obviously must be effective, but also be robust, scalable, and with product quality comparable to the original process. In this study, we report that three different GS−/− CHO cell lines developed in media containing a standard concentration of the selection agent methionine sulfoximine (MSX), but then exposed to increased MSX concentrations during seed train expansion, achieved titer increases of 10–19%. This result was observed in processes already considerably optimized. Expanding the cells with a higher MSX concentration improved cell line production stability with increased culture age. Production cultures in 500‐L and 1000‐L bioreactors replicated laboratory results using 5‐L bioreactors, demonstrating process robustness and scalability. Furthermore, product quality attributes of the final drug substance using the higher MSX process were comparable with those from cells expanded in media with the standard selection MSX concentration. Subsequent mechanistic investigations confirmed that the cells were not altered at the genetic level in terms of integration profiles or gene copy number, nor transcriptional levels of glutamine synthetase, heavy chain, or light chain genes. This study provides an effective and applicable strategy to improve the productivity of therapeutic proteins for biologics manufacturing.